PENGARUH KOMBINASI PAKAN TERHADAP PERTUMBUHAN DAN KELULUSAN HIDUP LARVA IKAN SELAIS (Ompok hypophthalmus) - Yurisman '; Benny Heltonika (Berkala Perikanan Terubuk, 2010)
This research was conducted from September to October 2008 in FishSeeding and Hatchery Laboratory Faculty of Fisheries and Marine Science,University of Riau. The aim of the research was to know the effect of the severalcombination feed on the growth and survival rate of Ompok hypophthalmuslarvae.A complete random design was applied with five treatments and threereplications : no combination (Artemia sp), combination Artemia sp and prawnpellet, Artemia sp and egg yolk, Artemia sp and tubifex sp, Artemia sp, egg yolk,Tubifex sp and prawn pellet. The result showed that the best treatment was feedingwith combination Artemia sp and Tubifex sp, larvae produced were 1,329 gr/ 30day, 60,5 mm/30 day and survival rate 75%. The water quality conditions were :water temperature 280 C, pH 5-6, dissolved oxygen 3,9- 5.6 mg/l.